Multiproduct cost passthrough: Edgeworth's paradox revisited - Armstrong, M; Vickers, J (University of Oxford, 2022)
Edgeworth's paradox of taxation occurs when an increase in the unit cost of a product causes a multiproduct monopolist to reduce prices. We give simple illustrations of the paradox, we show how it can arise with uniform pricing, and we give an analysis of the case of linear marginal cost and demand conditions. We show how the matrix of cost-passthrough terms must be similar to a positive definite matrix. When the firm supplies two substitute products we show how the paradox always occurs with a suitable choice of cost function. We then show a connection between Ramsey pricing and the paradox in a form relating to consumer surplus, and use it to find further examples where consumer surplus increases with cost.